A survey on the impact of the marketization of English on Parents’ attitudes to their young children learning English. - Đỗ, Thị Huyền (2020)
This study investigated the parents' attitudes towards their children' English language learning under the impact of marketization of English at some Primary schools in Khoai Chau district, Hung Yen province. A questionnaire survey was conducted by google.form and only 115 reponses of 350 parents were sent back. In addition, the author had four interviews through Zoom with four primary school leaders of different primary schools located in Hung Yen province and all these were recorded fully and exactly. Beside the data was collected by means of the questionnaire and interviewing, various information from advertisements on posters, leaflets, mass media such as facebook, websites, etc., was also collected as references of English training private companies’ marketing strategies. The results of the study showed the marketing strategies of these companies/centers had some positive and negative impacts on the parents’ attitudes but the positive ones overweigh the drawbacks. And from the findings, some implications are also drawn to school managers, parents as well as private education companies’ managers.